In vivo propagation of monoclonal antibodies in ascites fluid produced in BALB/c mice: characterization and diagnostic application for the identification of Vibrio cholerae O1 - Chowdhury, Mashiat Nawar (BRAC University, 2018)
This thesis report is submitted in partial fulfilment of the requirement for the degree of M.Sc. in Biotechnology, 2017.